Genome-wide identification and characterization of MdCYP86A family in apple - Hui-Min Lv; Rui-Han Qi; Zi-Han Yu; Yao-Yang Man; Yan-Hui Lv; Han Jiang; Tao Wang; Ya-Li Zhang; Yuan-Yuan Li (Fruit Research)
The cytochrome P450 enzyme is one of the largest protein families identified in cuticle biosynthesis, plant growth, development, and stress response. In the present study, 28 members of the MdCYP86A family were identified in apple (Malus × domestica Borkh.). Chromosomal localization analysis found that 28 genes were distributed on 13 chromosomes in apple. Phylogenetic and conserved motifs analysis showed that MdCYP86As in apple is evolutionarily most closely related to Arabidopsis thaliana. Each gene contains a cytochrome P450 domain, suggesting that MdCYP86As are highly conserved during the evolution of the species. Cis-acting element analysis of the promoter identified various elements associated with stress response. MdCYP86A21 was cloned in the apple genome to investigate the function of MdCYP86A family genes. MdCYP86A21 responded to abiotic stress, including PEG, NaCl, and ABA. The tissue-specific expression patterns revealed that the highest expression tissue was in flower by real-time quantitative reverse transcription (RT-qPCR). Subcellular localization showed that MdCYP86A21 was localized in the endoplasmic reticulum. Further, the function of MdCYP86A21 to enhance the resistance to PEG and NaCl stress in apple calli was verified. These results contribute to further study on the function of MdCYP86As and provide a molecular basis for the study of apple stress tolerance.